can anyone please help me solve this step by step by using the quadratic formula..

-4t^2-9t-3=0

3 answers

see below
t = -b/2a +/- (1/2a) sqrt (b^2 - 4 a c)
a = 4
b = 9 Note = I multiplied both side by -1
c = 3

t = -9/8 +/- (1/8) sqrt(81 - 48)

t = -9/8 +/- (1/8)sqrt (33)

t = [ -9+sqrt(33) ]/8
or
t = [ -9-sqrt(33) ]/8
DanH
I think you have a sign mistake
-b/2a = -(-9)/(-8) = -9/8
Similar Questions
  1. Josephine solved a quadratic equation: (x+6)^2=49. Her work is shown below.Step 1: √(x+6)^2 = √49 Step 2: x+6 = 7 Step 3: x
    1. answers icon 2 answers
  2. JamalStep 1: Set equation =0 . x2+4x−12=0 Step 2: Write quadratic equation as the product of two factors. (x+6)(x−2)=0 Step
    1. answers icon 2 answers
    1. answers icon 1 answer
  3. Consider the sequence of steps to solve the equation:5(x - 3) = 7x2 Step 1 ⇒ 10(x - 3) = 7x Step 2 ⇒ 10x - 30 = 7x Step 3
    1. answers icon 3 answers
more similar questions